Microclimates growing and watering volumes influences the physiological traits of chili pepper cultivars in combating abiotic stress - Farhan Ahmad; Kusumiyati Kusumiyati; Mochamad Arief Soleh; Muhammad Rabnawaz Khan; Ristina Siti Sundari (Scientific Reports)
Abstract Chili peppers are a staple food for countries worldwide and are loaded with vitamins and antioxidants. One of the world’s largest chili consumers, Indonesia faces climate adversities and cash-crop pest infestations that affect its horticulture market. The present research explores microclimatic and watering for physiological performances in different chili cultivars, useful in suggesting the strategies of cultivation with a climate-resilient perception. The research was done in the Bale Tatanen, Padjadjaran University, using a Factorial Randomized Complete Block Design to analyze chili plant physiology. According to statistical analyses, cultivars did not significantly affect absolute growth rate (AGR), but growing microclimates and watering volumes did significantly affect AGR and water use efficiency (WUE). The rain shelter and screen house had the highest WUE and AGR values. Growing microclimates and cultivars significantly affected transpiration rate, stomatal conductance to water vapor and total conductance to CO2, with the screen house exhibiting the highest values. All three factors significantly affected the photosynthetic rate, with the greenhouse showing the highest rate. The photosynthetic photon flux density (PPFD) was likewise highest in the greenhouse. This study aimed to systematically assess these factors and it tried suggesting practices that might assist in combating the effects of abiotic stress on chili production, for its sustainability. The findings of this research would help in conceptualizing the most efficient microclimate and watering volume for chili cultivation particularly, when considering climate change challenges as well; these results could also be applied to develop guidelines which might serve helpful at resource-poor farming.